A Multi-National Questionnaire-Based Analysis of Dental Students’ Knowledge of the Management of Deep Caries and the Exposed Pulp - Venkateshbabu Nagendrababu; Arindam Dutta; Ana Arias; Aleksandar Jakovljevic; Ahmed Hieawy; Frank C. Setzer; Jugoslav Ilic; Milos Beloica; Meric Karapinar Kazandag; Nandini Suresh; Paul V. Abbott; Raghavendra M. Shetty; et al. (International Dental Journal)
Introduction and aims: To evaluate knowledge regarding the management of deep carious lesions and exposed pulps among undergraduate and postgraduate endodontic students from ten dental institutions across ten countries, and the impact of operator (material, antibiotic prescription) and patient-related (age, symptoms) factors on their treatment protocols. Methods: An online questionnaire was distributed to evaluate student knowledge of the management of deep caries and exposed pulp related to four clinical scenarios. Simple descriptive statistics were used to describe the data and McNemar tests were employed to identify significant differences between the scenarios. The P-value was set at 5%. Results: A total of 435 undergraduates and 139 postgraduates from ten dental schools participated in this survey. The final survey included 401 responses from undergraduates and 127 from postgraduates for statistical analysis. When symptoms were present, the majority of undergraduate and postgraduate students preferred non-selective (complete) caries removal over selective (partial) caries removal in young patients. The majority of postgraduates preferred partial pulpotomy in younger patients and pulpectomy and root canal treatment (RCT) in older patients. The majority of undergraduates preferred pulpectomy and RCT in both young/old patients when symptoms were present. The majority of undergraduates and postgraduates opted for mineral trioxide aggregate and Biodentine, respectively, when treating the exposed pulp. Systemic antibiotics were not recommended by both undergraduates and postgraduates, regardless of the patient's age and symptoms. Conclusion: Among the scenarios surveyed, the majority of undergraduates and postgraduates preferred: a) pulpectomy and RCT for older patients in the presence or absence of symptoms; b) hydraulic calcium silicate cements as pulp capping material; and c) did not recommend systemic antibiotics. Clinical relevance: The majority of students choose non-selective (complete) caries removal in all cases and if the pulp is exposed, the use of hydraulic calcium silicate cements iwas the preferred material. Systemic antibiotics are considered unnecessary, irrespective of the patient's age and symptoms.